Soil CO2 and N2O emissions and microbial abundances altered by temperature rise and nitrogen addition in active-layer soils of permafrost peatland - Song, Yanyu; Cheng, Xiaofeng; Song, Changchun; Li, Mengting; Gao, Siqi; Liu, Zhendi; Gao, Jinli; Wang, Xianwei (Frontiers in Microbiology, 2022)
Changes in soil CO2 and N2O emissions due to climate change and nitrogen input will result in increased levels of atmospheric CO2 and N2O, thereby feeding back into Earth’s climate. Understanding the responses of soil carbon and nitrogen emissions mediated by microbe from permafrost peatland to temperature rising is important for modelling the regional carbon and nitrogen balance. This study conducted a laboratory incubation experiment at 15 °C and 20 °C to observe the impact of increasing temperature on soil CO2, N2O emissions and soil microbial abundances in permafrost peatland. An NH4NO3 solution was added to soil at a concentration of 50 mg N kg−1 to investigate the effect of nitrogen addition. The results indicated that elevated temperature, available nitrogen and their combined effects significantly increased CO2 and N2O emissions in permafrost peatland. However, the temperature sensitivities of soil CO2 and N2O emissions were not affected by nitrogen addition. Warming significantly increased the abundances of methanogens, methanotrophs, nirK-type denitrifiers, and the contents of soil dissolved organic carbon (DOC), ammonia nitrogen, whereas nirS-type denitrifiers, β-1,4-glucosidase (βG), cellobiohydrolase (CBH), and acid phosphatase (AP) activities significantly decreased. Nitrogen addition significantly increased soil nirS-type denitrifiers abundances, β-1,4-N- acetylglucosaminidase (NAG) activities and ammonia nitrogen, nitrate nitrogen contents, but significantly reduced bacterial, methanogen abundances, CBH, and AP activities. A rising temperature and nitrogen addition had synergistic effects on soil fungal and methanotroph abundances, NAG activities, and DOC, DON contents. Soil CO2 emissions showed a significantly positive correlation with soil fungal abundances, NAG activities, ammonia nitrogen and nitrate nitrogen contents. Soil N2O emissions showed positive correlations with soil fungal, methanotroph, nirK -type denitrifiers abundances, DOC, ammonia nitrogen, and nitrate contents. These results demonstrate the importance of soil microbes, labile carbon, and nitrogen for regulating soil carbon and nitrogen emissions. The results of this study can assist simulating the effects of global climate change on carbon and nitrogen cycling in permafrost peatlands.